WORKSHOP /DISEMINASI PEMBELAJARAN DIGITAL: PEMANFAATAN ZOOM, WORDWALL GAME, CANVA, DAN SMART PRESENTATIONS DALAM PEMBELAJARAN DI SMP MUHAMMADIYAH JAYAPURA ABEPURA: WORKSHOP / DISSEMINATION OF DIGITAL LEARNING: THE UTILIZATION OF ZOOM, WORDWALL GAME, CANVA, AND SMART PRESENTATIONS IN LEARNING AT SMP MUHAMMADIYAH JAYAPURA ABEPURA - Irfun Irfun; Muhammad Nur Jaya; Ismail Maswatu (LPPM Universitas Muhammadiyah Papua, 2026)
This Community Service Program (PKM) aims to enhance the competencies of teachers at SMP Muhammadiyah Jayapura Abepura in utilizing digital technology for innovative and interactive learning. Through a digital learning workshop and dissemination activities, participants were equipped with practical skills in using the Zoom platform for online learning, Wordwall Game to create quizzes and educational games, Canva to design engaging visual teaching materials, and Smart Presentations as an effective presentation medium. The implementation methods included training sessions, demonstrations, and hands-on practice, with a focus on strengthening teachers’ digital skills. The results indicate a significant improvement in participants’ understanding and ability to integrate technology into the learning process. This program is expected to support digital transformation within the school environment and encourage the creation of more active, creative, and enjoyable learning experiences for students.